Prenatal and fetal diagnosis of trisomy 18 after low‐risk cell‐free fetal DNA screening: A report of four cases. (29th November 2022) - Sheehan, Elizabeth; Bacon, Victoria; Lascurain, Seth; Stone, Julia; Yatsenko, Svetlana; Aarabi, Mahmoud; Skvarca, Lauren B.; Clemens, Michele; Saller, Devereux
Abstract: Introduction: Non‐Invasive Prenatal Screening (NIPS) is a useful screening method for common aneuploidies that can occur in pregnancies. It yields high sensitivities and specificities for the targeted conditions it tests for. Most commonly, these include Trisomies in chromosomes 21, 18, and 13, as well as aneuploidies in chromosomes X and Y. It does not, however, replace diagnostic testing. We review four cases seen by our institutions of patients who had NIPS performed with low‐risk results and subsequently had fetuses affected with trisomy 18. Methods: All fetal samples were evaluated by level II anatomic ultrasound and tested on amniocytes or products of conception through karyotype or chromosomal microarray following low‐risk NIPS. Results: None of the fetuses showed evidence of mosaicism and had features (both on ultrasound and postnatally) consistent with Trisomy 18. Postnatal fluorescence in situ hybridization performed on Formalin‐Fixed Paraffin‐Embedded tissue from 3 of the affected pregnancies' placentas identified mosaicism of trisomy 18. Discussion: We discuss the possible explanations for the discrepancy between NIPS results and fetal karyotype, including, but not limited to placental mosaicism, placental size, and limitations of NIPS as a screening test. Key points: What is already known about this topic? Cell‐free DNA is a screening test for common aneuploidies Screening tests can generate false positive and false negative results There are more cases of false positive cases than false negative cases following cell‐free DNA screening What does this study add? Demonstrates four cases of full fetal Trisomy 18 after low‐risk cell‐free DNA screening, adding to the literature surrounding false negative cases Placental fluorescence in situ hybridization (FISH) was obtained in 3 cases showing mosaicism not seen in the affected fetus/neonate